Comparison of baseline characteristics of African‐American/black and non‐Hispanic white family caregivers in Tele‐Savvy: An online psychoeducation program: Dementia care research (research projects; nonpharmacological) / Behavioral interventions. (7th December 2020) - Bonds, Kalisha; Griffiths, Patricia; Higgins, Melinda; Nocera, Joe R; Epps, Fayron; Brewster, Glenna S; Hepburn, Kenneth
Abstract: Background: Tele‐Savvy is an NIA‐funded 3‐arm randomized controlled longitudinal trial of a fully online psychoeducation program. Tele‐Savvy is specifically designed to promote caregiver mastery by enhancing caregivers' abilities to manage daily challenges to reduce caregiver distress. Method: This presentation reports on the baseline characteristics of 209 family caregivers (159 non‐Hispanic White [NHW] and 50 African American/Black [AA] family caregivers). Bivariate analysis was conducted to compare group differences among AA and NHW family caregivers. Result: AA caregivers reported their persons living with Alzheimer's disease and related dementias (AD/ADRD; PWD) were more dependent. AA caregivers reported their PWDs had significantly worse performance of activities of daily living (e.g., toileting, grooming) ( p < .001) and significantly worse performance of instrumental activities of daily living (e.g., transportation, managing finances) ( p = .007). AA caregivers reported their PWDs had significantly more disruptive behaviors ( p = .010) and significantly worse neuropsychiatric behaviors (e.g., delusions, disinhibition) ( p = .025) than were reported by NHW caregivers regarding their PWDs. In addition, AA caregivers reported better caregiving experiences. AA caregivers reported significantly less personal strain ( p = .019), significantly better caregiver competence ( p < .001), significantly better management of their caregiving situation ( p = .001), and significantly better management of the behavioral symptoms associated with AD/ADRD ( p = .009) than NHW caregivers. AA caregivers reported significantly better mindful self‐care in the domain of self‐compassion and purpose (i.e., a sense of meaning when getting through difficult situations) ( p = .015) compared to NHW caregivers. Conclusion: AA caregivers recruited into Tele‐Savvy have reported quantitative baseline characteristics similar to previous caregiving studies, which portray AA caregivers as less distressed and better prepared for AD/ADRD caregiving than NHW caregivers. This longitudinal study will enable us to see if AA and NHW caregivers change on these dimensions over time in similar or different ways. We will interview some of the caregivers to see if AA and NHW caregivers experience similar or different patterns of distress than explained through quantitative measures. Continuation in Tele‐Savvy will provide an opportunity to assess the extent to which both groups respond to the intervention.